Language in mathematical education : Research and practice - Durkin, Kevin; Shire, Beatrice (Philadelphia : Open University press, 1991)
Concerned with various aspects of language in mathematics education, this book aims to reveal some of the ambiguities and complexities in the way language is used in the mathematics curriculum. It aims to present current perspectives and review key issues in mathematics education
Includes bibliographical references (p. [256]-271) and indexes.
Keywords: Mathematics -- Study and teaching; Language and education